Prototypical Anger Components: A Multilevel Study. (November 2014) - Fernandez, Itziar; Carrera, Pilar; Paez, Dario; Alonso-Arbiol, Itziar; Campos, Miryam; Basabe, Nekane
This study explored the effects of psychological and cultural variables on self-reported emotional prototypes of anger. Eight anger components were examined using a multilevel analysis. Competitiveness, interdependence, gender, instrumentality, and expressivity were entered as individual variables, and individualism/collectivism, masculinity/femininity, and the Human Development Index (HDI) were entered as cultural variables. All highlight the importance of considering simultaneously the individual and social levels, with a view to gaining more in-depth knowledge of the emotions. Data were collected among 5, 006 college students from 25 countries. Being female, instrumentality, HDI, and the interaction between country-level HDI competitiveness predicted internal processes and behavioral outcomes of anger prototypes. Expressivity, instrumentality, country-level masculinity, and the interaction between gender and country-level masculinity predicted self-control mechanisms of anger prototypes. It is concluded that salient differences in anger prototypes can be found at both individual and country level, and that interaction effects of HDI with individual variables are essential in understanding anger prototypes.